The Effect Of A Proposed Training Program Using Modern Technology In Developing The Swan Diving Skill Of School Volleyball Team Players - CHOUFI, Housseyn; Zeroual, Mohammed; kenioua, Mouloud (Journal of Sport Science Technology and Physical Activities, 2022)
The Object of the study aims to investigate the effect of a proposed training program using the Kinovea software in developing the swan diving skill of the school volleyball team players. For this purpose, we used the experimental method. On a sample composed of 12 players, were randomly divided into Four equal groups (3 experimental groups and a control group). Chosen as Intentionally, each experimental group used one of the three technology methods (watching a replay of the self-performance video or watching a video of the ideal model or watching both at the same time). and for data collection, we used the swan diving skill test. After collecting the results and having treated them statistically, we conclude that the Kinovea software had a positive effect in developing the swan diving skill. the method of watch the video replay of the self-performance was the best. That is why coaches should focus on it.